Could L2 Lexical Attrition Be Predicted in the Dimension of Valence, Arousal, and Dominance? - Ni, Chuanbin; Jin, Xiaobing (Frontiers in Psychology, 2020)
The current study attended to predict L2 lexical attrition by means of Decision Tree model in three emotional dimensions, that is, the valence dimension, the arousal dimension, and the dominance dimension. A sample of 188 participants whose L1 was Chinese and L2 was English performed a recognition test of 500 words for measuring the L2 lexical attrition. The findings explored by the Decision Tree model indicated that L2 lexical attrition could be predicted in all the three emotional dimensions in two aspects: (1) among the three emotional dimensions, the valence dimension was the most powerful in predicting L2 lexical attrition, followed successively by the dominance dimension and the arousal dimension; (2) most of the neutral words in the three emotional dimensions were predicted to be inferior to emotional words in L2 attrition. In addition, the modified Revised Hierarchical Model for emotion could be adopted to justify the modulation of the emotion-memory effects upon L2 lexical attrition.